Post-fire plant diversity and abundance in pine and eucalypt stands in Portugal: effects of biogeography, topography, forest type and post-fire management - Maia, P.
This study concerned the mid-term regeneration of the woody understory vegetation of pure and mixed stands of Pinus pinaster Ait. and Eucalyptus globulus Labill. in northern and central Portugal following wildfires in 2005 and 2006. Pine and eucalypt stands are the most widespread and most fire-prone forest types in Portugal. The main aim was to investigate the importance of biogeography, topography, forest type and post-fire management operations in explaining the patterns in shrub diversity (species richness) and abundance (cover). To this end, 284 study sites in four distinct biogeographic regions were sampled 5 to 7years following the last wildfire. At each site, the presence and cover of individual shrub species were estimated using 4 sub-plot of approximately 10m2 each. The entire data set was analyzed by means of GLM using a total of seven explanatory variables: biogeographic region, forest type, three types post-fire management operations (soil tillage, tree harvesting, and shrub clearance), and two topographic variables (slope angle and elevation). The GLM analysis was also done for the individual biogeographic regions.Biogeographic region and slope steepness were key factors explaining shrub species richness, albeit the role of slope angle was possibly linked to the intensity of past land use.Biogeographic region equally played a significant role in explaining the cover of all shrubs together as well as of the shrubs of Leguminosae and Cistaceae. All three types of post-fire management operations appeared to hamper the recovery of resprouters and Leguminosae, whereas just tree harvesting and shrub clearance (but not soil tillage) negatively affected the cover of seeder species. These impacts of post-fire management operations had a noticeable region-specific component, being more relevant in the less productive biogeographic regions.Also the role of forest type depended strongly on biogeographic region. It was only significant in the South Mediterranean region, where pine plantations had a higher total shrub cover as well as higher covers of seeders and Cistaceae. Possibly, however, this significant role of forest type could be due to the lower incidence of shrub clearance in the pine stands.